2017
DOI: 10.1016/j.celrep.2016.12.054
|View full text |Cite
|
Sign up to set email alerts
|

MLL-AF4 Spreading Identifies Binding Sites that Are Distinct from Super-Enhancers and that Govern Sensitivity to DOT1L Inhibition in Leukemia

Abstract: SummaryUnderstanding the underlying molecular mechanisms of defined cancers is crucial for effective personalized therapies. Translocations of the mixed-lineage leukemia (MLL) gene produce fusion proteins such as MLL-AF4 that disrupt epigenetic pathways and cause poor-prognosis leukemias. Here, we find that at a subset of gene targets, MLL-AF4 binding spreads into the gene body and is associated with the spreading of Menin binding, increased transcription, increased H3K79 methylation (H3K79me2/3), a disruption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
141
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(153 citation statements)
references
References 40 publications
(84 reference statements)
11
141
1
Order By: Relevance
“…To verify this, we assessed MLL occupancy at Hox genes in lin 2 cells harvested from Psip1-depleted cells through ChIP-qPCR. In line with earlier reports, 24,41 ChIP-qPCR analyses demonstrated that MLL occupancy at HoxA9 and HoxA7 promoters was decreased about twofold in Psip…”
Section: Hoxa9 and Eya1 In Psipsupporting
confidence: 92%
See 2 more Smart Citations
“…To verify this, we assessed MLL occupancy at Hox genes in lin 2 cells harvested from Psip1-depleted cells through ChIP-qPCR. In line with earlier reports, 24,41 ChIP-qPCR analyses demonstrated that MLL occupancy at HoxA9 and HoxA7 promoters was decreased about twofold in Psip…”
Section: Hoxa9 and Eya1 In Psipsupporting
confidence: 92%
“…Several studies show that the latter tethers wild-type MLL and/or MLL-FP complexes to chromatin ( Figure 1A). 16,24,41 Several approaches have been taken to interfere with the function of MLL-fusion complexes, including DOT1L or BET protein inhibitors that target the fusion moiety of MLL-FPs. [47][48][49][50] On the other hand, others directly target the MLL fragment of the fusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatin Immunoprecipitation. ChIP-qPCR and ChIP-seq experiments were conducted as previously described 49,83 . Briefly, double-fixed samples (2 mM disuccinimidyl glutarate (Sigma) for 30 min followed by 1 % formaldehyde (Sigma) for 30 min) were sonicated in batches of 10 7 cells using a Covaris (Woburn, MA) following the manufacturer's recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the direct effects of BRD4 inhibition, we chose a 90 min IBET treatment time, based on the qRT-PCR data. We analyzed the global transcriptional response to IBET by sequencing nascent RNA 49 , which provides a much more direct measure of transcriptional output compared to steady state RNA-seq (Fig 2b, Supplementary Table 2). As a comparison, we also sequenced nascent RNA following 24h IBET treatment (Fig 2b, Supplementary Table 2).…”
Section: Loss Of Bet and Mediator Binding Is Associated With Large Trmentioning
confidence: 99%